Intercellular Vesicular Transfer by Exosomes, Microparticles and Oncosomes - Implications for Cancer Biology and Treatments - Jaiswal, Ritu; Sedger, Lisa M. (Frontiers in Oncology, 2019)
Intercellular communication is a normal feature of most physiological interactions between cells in healthy organisms. While cells communicate directly through intimate physiology contact, other mechanisms of communication exist, such as through the influence of soluble mediators such as growth factors, cytokines and chemokines. There is, however, yet another mechanisms of intercellular communication that permits the exchange of information between cells through extracellular vesicles (EVs). EVs are microscopic (50 nm -10 μM) phospholipid bilayer enclosed entities produced by virtually all eukaryotic cells. EVs are abundant in the intracellular space and are present at a cells’ normal microenvironment. Irrespective of the EV ‘donor’ cell type, or the mechanism of EV biogenesis and production, or the size and EV composition, cancer cells have the potential to utilize EVs in a manner that enhances their survival. For example, cancer cell EV overproduction confers benefits to tumor growth, and tumor metastasis, compared with neighbouring healthy cells. Herein, we summarize the current status of knowledge on different populations of EVs. We review the situations that regulate EV release, and the factors that instruct differential packaging or sorting of EV content. We then highlight the functions of cancer-cell derived EVs as they impact on cancer outcomes, promoting tumor progression, metastases, and the mechanisms by which they facilitate the creation of a pre-metastatic niche. The review finishes by focusing on the beneficial features of tumor-derived EVs that can be adapted and utilized for cancer treatments, including those already being investigated in human clinical trials.